Закономерности повышения скорости нарастания разрядных токов в нагрузке при ограничении их максимальных значений - Щерба, А.А.; Супруновская, Н.И. (Технічна електродинаміка, 2012)
The regularities of increasing of rate of current rise in the circuit of capacitor discharge on the load at increasing its capacity and limiting of maximal discharging current value are studied. The behavior of durations of pulse currents in the load is studied and possibilities of increasing of frequency charging-discharging capacitor during such regulation of rate of discharge current rise are shown.